2014
DOI: 10.4028/www.scientific.net/amm.660.949
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of Lean and Cleaner Production – A Preliminary Study for Malaysia Manufacturing Industry

Abstract: Adoption of lean production in managing the production operations with a cleaner production due to of environmental concerns positively drive new manufacturing paradigm in the manufacturing environment. This leads to this study being carried out, in order to investigate the extent of which these practices has been adopted in Malaysia’s manufacturing industry. The finding revealed that good performance in environmental practice in tandem with the appraisal of labour safety in material handling has helped the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Pioneer survey researches in Malaysia manufacturing settings had reported the level of LM adoption by local manufacturers was moderate (Nordin, Md Deros, & Abd Wahab, 2010b;Puvanasvaran et al, 2008;Wong et al, 2009). Nevertheless, Malaysian manufacturers continue to show high tendency of implementing LMS to pursue improvement in terms of product quality and durability according to a more recent survey (Yusup, Wan Mahmood, Salleh, & Mohd Yusof, 2014). As per the growing interest, federal government through Malaysia Productivity Corporation (MPC) also have set interest and demonstrated commitment on Lean Management since 2011.…”
Section: Lean Manufacturing Scenario In Malaysiamentioning
confidence: 99%
“…Pioneer survey researches in Malaysia manufacturing settings had reported the level of LM adoption by local manufacturers was moderate (Nordin, Md Deros, & Abd Wahab, 2010b;Puvanasvaran et al, 2008;Wong et al, 2009). Nevertheless, Malaysian manufacturers continue to show high tendency of implementing LMS to pursue improvement in terms of product quality and durability according to a more recent survey (Yusup, Wan Mahmood, Salleh, & Mohd Yusof, 2014). As per the growing interest, federal government through Malaysia Productivity Corporation (MPC) also have set interest and demonstrated commitment on Lean Management since 2011.…”
Section: Lean Manufacturing Scenario In Malaysiamentioning
confidence: 99%
“…Based on the research conducted by Yusup et al [26] it has been found that there is a strong correlation between lean and clean production practices, and the selection of production equipment affects the improvement of the working condition in shop-floor that facilitate the lean and clean production practice. Another research done by Iranmanesh et al [27] revealed that production equipment has a significant impact on sustainable performance, and the authors also claim that having lean culture moderates the impact of production equipment on sustainable performance.…”
Section: Production Equipment and Sustainable Production Systemmentioning
confidence: 99%
“…Further, initiatives like lean manufacturing and six sigma targeted towards improving the overall operational performance of a firm through minimisation of non-value-adding activities and waste also contribute towards sustainability in manufacturing (e.g. Yusup et al ., 2014; Abualfaraa et al ., 2020). All such SM-related actions, initiatives, techniques and programmes that enable manufacturing firms to incorporate sustainability in their products, processes and systems are widely known as sustainable manufacturing practices (SMPs) (Alayon et al ., 2016; Huang, 2017).…”
Section: Introductionmentioning
confidence: 99%